ANALISIS DAMPAK PERUBAHAN CURAH HUJAN, LUAS TAMBAK GARAM DAN JUMLAH PETANI GARAM TERHADAP PRODUKSI USAHA GARAM RAKYAT DI KECAMATAN JUWANA KABUPATEN PATI PERIODE 2003-2012 - Yudha Adiraga; Achma Hendra Setiawan (Universitas Diponegoro, 2014)
This research is motivated by the inability of the local salt production to supply the needs of national salt for consumption and industrial purpose has prompted the government to import salt. As for the problem of this research is